Antinociceptive effect of free and liposome encapsulated piroxicam in experimental animals - Mohd Safwan bin Abdul Ghani
Piroxicam is a non-steroidal anti-inflammatory drug (NSAID) which exhibits anti-inflammatory, analgesic and anti-pyretic properties. Whereas liposome is lipid bilayers surrounding an aqueous solution which can improve therapeutic and pharmacological effects of encapsulated drugs by increasing their bioavailability in body. It is early assumed that liposome-encapsulated piroxicam exhibit higher anti-nociceptive effect than free piroxicam when administered orally into experimental animals. The present study is carried out to evaluate the level of anti-nociceptive properties exhibited by piroxicam and liposome-encapsulated piroxicam using different models of nociception. liposome-encapsulated piroxicam is prepared initially using proliposome method, which based on the conversion of initial concentrated phospholipid mixture into liposomal dispersion by dilution under strictly controlled conditions. Four types of animal models will be used to evaluate the anti-nociceptive effects of piroxicam and liposome-encapsulated piroxicam. The models of nociception suggested are acetic acid-induced abdominal writhing test, plantar test, formalin induced paw-licking test and Randall-Sellito test. Appropriate doses were administered orally to mice or rats according to each test. Data collected are analyzed using SPSS to compare the level of efficacy among treatment groups with different drug concentrations respectively. For abdominal writhing test, minimum inhibition of 22.90% was achieved in 0.3 mg/kg free piroxicam while maximum inhibition of 82.10% was pulled off in 30 mg/kg liposome encapsulated piroxicam. For formalin test, liposome encapsulated piroxicam produced significant effect of all dosage (0.3, 3.0, 30 mg/kg) when compared to control, with percentage of inhibition 25.59%, 47.46%, 81.36% respectively. For Randall and Sellito test, significant differences between free and liposome encapsulated piroxicam was shown at 30 mg/kg dosage with percentage reduction at 55.81% respectively. For plantar test, when compared to control, 3.0 and 30 mg/kg both free and liposome encapsulated piroxicam had significant percentage of inhibition with highest value 39.76% and the lowest value 30.77%. In low dosage of treatment (0.3 mg/kg) liposome encapsulated piroxicam exhibited early onset of pain inhibition with continuos action when compared with both control and free drug at the same dosage. Besides, all results did produce the same consistent inhibition activity of liposome encapsulated piroxicam, which were better than non-encapsulated one. As conclusion, liposome encapsulated piroxicam is proved to exhibit better antinociceptive activity than free piroxicam.